Experimental and numerical investigation on thermal performance of enhanced geothermal system: A case study of Guanzhong basin - Guoyao Jin; Yuxiang Zhao; Ye Min; Xiao Zhang; Chao Jiang; Zijing Tan (Case Studies in Thermal Engineering)
Escalating global energy demands and environmental concerns have positioned Hot Dry Rock as a pivotal renewable energy source. This study investigates the thermal performance of Enhanced Geothermal Systems in the Guanzhong Basin, China, integrating experimental measurements and numerical simulations to evaluate heat extraction dynamics. While the findings are context-specific to the Guanzhong Basin's sedimentary geology—characterized by a geothermal gradient and fracture apertures. The methodology establishes transferable principles for Enhanced Geothermal Systems design in analogous basins. Key results demonstrate that optimized fracture configurations (connectivity, aperture) and controlled injection parameters (flow rates of 10–12 kg/s, well spacings of 250–400 m) significantly enhance energy extraction efficiency by mitigating thermal short-circuiting. A multi-objective genetic algorithm correlates operational variables with extraction efficiency, providing a quantitative framework for optimization. The study advances a replicable evaluation methodology, incorporating energy, economic, and environmental metrics, to guide sustainable Hot Dry Rock exploitation in fracture-dominated sedimentary systems.